2004
DOI: 10.1111/j.0013-9580.2004.66003.x
|View full text |Cite
|
Sign up to set email alerts
|

The Nonmalformed Hemisphere Is Secondarily Impaired in Young Children with Hemimegalencephaly: A Pre‐ and Postsurgery Study with SPECT and EEG

Abstract: Summary:Purpose: To study separately the functional value of each cerebral hemisphere in hemimegalencephaly (HME). HME is a unique model of unilateral hemispheric lesion, but one suspects that the non-HME hemisphere also could be functionally impaired because the postsurgery outcome is less favorable than expected.Methods: We performed simultaneous prolonged EEG and 133-xenon SPECT (single-photon emission computed tomography); we measured the absolute values of cerebral blood flow (CBF) in both hemispheres and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…The diaschisis phenomenon has been proposed to account for the finding that focal cortical resection around the epileptogenic lesion, or hemispheric disconnection, can restore the contralateral hemisphere's functional and hemodynamic maturation. 16,[55][56][57] It will be important to determine whether impairments in interhemispheric temporal lobe connectivity impact on the development of verbal skills, as has been reported for cohorts of children with perinatal pathology. 58,59 In conclusion, an impairment of temporal lobe maturation is a likely sequela of WS.…”
Section: Discussionmentioning
confidence: 99%
“…The diaschisis phenomenon has been proposed to account for the finding that focal cortical resection around the epileptogenic lesion, or hemispheric disconnection, can restore the contralateral hemisphere's functional and hemodynamic maturation. 16,[55][56][57] It will be important to determine whether impairments in interhemispheric temporal lobe connectivity impact on the development of verbal skills, as has been reported for cohorts of children with perinatal pathology. 58,59 In conclusion, an impairment of temporal lobe maturation is a likely sequela of WS.…”
Section: Discussionmentioning
confidence: 99%
“…The intrauterine excessive fetal movement and hiccups were likely manifestations of intrauterine seizure activity [11]. Rapidly progressing clinical and EEG abnormalities raised concern for irreversible injury to the more normal-appearing right hemisphere, as a result of epileptogenic bombardment from the abnormal hemisphere [13,16,17,18,19]. The proposed mechanism of this injury has been decreased oxygenation of the more normal hemisphere by a steal-like phenomenon [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Rapidly progressing clinical and EEG abnormalities raised concern for irreversible injury to the more normal-appearing right hemisphere, as a result of epileptogenic bombardment from the abnormal hemisphere [13,16,17,18,19]. The proposed mechanism of this injury has been decreased oxygenation of the more normal hemisphere by a steal-like phenomenon [18, 19]. Alfonso et al [19], using near-infrared spectroscopy (SPECT), found bilateral decreased oxygen saturation in a 3-week-old with tuberous sclerosis and hemimegalencephaly; this was interpreted as being due to increased oxygen consumption by the abnormal brain with decreased availability of oxygen to the normal hemisphere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical resection of facial lipomatosis is difficult because of infiltration and lack of encapsulation; it usually requires re-intervention (Unal et al, 2000). Early extensive resection or surgical disconnection of the epileptogenic dysplastic hemisphere also may favor improved outcome by protecting the contralateral hemisphere from spreading of electrical activity (Soufflet et al, 2004). It may control severe epilepsy and preserve the development of higher cortical functions in the more normal contralateral hemisphere (Humbertclaude et al, 1997).…”
Section: Managementmentioning
confidence: 99%